The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.pmedr.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a food insecurity screening and referral program in student-run free clinics in San Diego, California

Abstract: Food insecurity is associated with many poor health outcomes yet is not routinely addressed in clinical settings. The purpose of this study was to implement a food insecurity screening and referral program in Student-run Free Clinics (SRFC) and to document the prevalence of food insecurity screening in this low-income patient population. All patients seen in three SRFC sites affiliated with one institution in San Diego, California were screened for food insecurity using the 6-item United States Department of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 20 publications
(29 reference statements)
0
73
0
10
Order By: Relevance
“…[26][27][28][29][30][31][32][33] The remainder of the studies had descriptive, mixed methods, or qualitative designs (n = 7, 30%). Some articles focused on specific patient populations: 9 studies evaluated interventions targeting adult caregivers of pediatric patients (39%), 16,21,22,28,29,31,[34][35][36] 1 targeted adolescents (4%), 37 2 focused on pregnant women (9%), 18,24 5 focused on patients with diabetes 27,30,32,33,39 or another chronic condition 25 (22%), and 1 focused on patients with cancer (4%). 38 Seventeen studies (74%) were considered low 17,26,28,30,31,32,37 or very low quality 18,27,29,[33][34][35][36][38][39][40] and 6 (26%) studies were rated moderate quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31][32][33] The remainder of the studies had descriptive, mixed methods, or qualitative designs (n = 7, 30%). Some articles focused on specific patient populations: 9 studies evaluated interventions targeting adult caregivers of pediatric patients (39%), 16,21,22,28,29,31,[34][35][36] 1 targeted adolescents (4%), 37 2 focused on pregnant women (9%), 18,24 5 focused on patients with diabetes 27,30,32,33,39 or another chronic condition 25 (22%), and 1 focused on patients with cancer (4%). 38 Seventeen studies (74%) were considered low 17,26,28,30,31,32,37 or very low quality 18,27,29,[33][34][35][36][38][39][40] and 6 (26%) studies were rated moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…21,24,28,29,34,37 We combined passive (resource information provided) and active (assistance contacting resource) referral interventions into 1 category as results were too heterogenous to make meaningful comparisons between the 2 referral types. A second group included 10 studies (43%) examining interventions that provided food or food vouchers in addition to resource referrals 17,18,25,26,[31][32][33]36,38,39 and 1 study that provided food without referrals to community food resources. 23 Included studies examined outcomes ranging from: (1) process outcomes (eg, number of patients referred), (2) food security status, (3) health, (4) health behaviors and self-efficacy, (5) health care utilization and/ or cost, and (6) patient/caregiver perception of intervention acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…Though several reviewed articles noted resources needed to implement FI screening, 11,21,35,37,43 none of the studies we identified provided specific estimates of screening costs or compared costs to the health benefits and/ or cost savings that FI screening efforts might yield. Several studies relied on RAs, 11…”
Section: • Screening Costsmentioning
confidence: 99%
“…O entendimento da SAN dentro do quadro teórico da determinação social da saúde também foi previsto . Finalmente, considerando a trajetória da epidemiologia e o movimento de pautar questões de saúde exclusivamente em associações probabilísticas (Krieger, 1994) [5, 9, 10, 13, 14, 16, 17, 18, 19, 20, 23, 24, 25, 27, 2004 2005 2006 2007 2008 2009 28,29,30,31,32,34,35,36,37,38,40,42,43,44,45,47,48,50,51,52,53] Adicionalmente, sete autores utilizam genericamente a expressão fator de risco [23,34,35,40,47,52,53], enquanto outros sete qualificam como risco psicossocial [9,14,19,20,27,29,48], dois como risco social [10,45], um como risco relacionado ao estilo de vida [25] e nos demais não há especificação. A noção de SAN como uma necessidade está presente em 15 publicações [5,9,10,13,…”
Section: Síntese Dos Achadosunclassified
“…A noção de SAN como uma necessidade está presente em 15 publicações [5,9,10,13,17,18,20,27,29,31,37,40,42,43,45], com sete especificando-a como uma necessidade no domínio social [10,13,18,20,31,42,43]. Sete designam a SAN como um problema social relacionado à saúde [14,16,24,30,31,32,42] e dois como um problema clínico a ser diagnosticado e tratado na APS [38,52]. Em apenas oito publicações se reconhece a associação da IAN com a pobreza/baixa renda [18,19,25,32,34,42,43,51] e em três com restrições financeiras [10,40,42], mas sem indicação explícita de causalidade.…”
Section: Síntese Dos Achadosunclassified